2014
DOI: 10.1016/j.geomphys.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Black brane solutions governed by fluxbrane polynomials

Abstract: A family of composite black brane solutions in the model with scalar fields and fields of forms is presented. The metric of any solution is defined on a manifold which contains a product of several Ricci-flat "internal" spaces. The solutions are governed by moduli functions H_s (s = 1, ..., m) obeying non-linear differential equations with certain boundary conditions imposed. These master equations are equivalent to Toda-like equations and depend upon the non-degenerate (m x m) matrix A. It was conjectured ear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 37 publications
1
33
0
3
Order By: Relevance
“…Note that the parameters γ = (γ 1 , γ 2 ) are nothing but the components of the dual Weyl vector for given Lie algebra with the Cartan matrix (18). They may be represented in a explicitly symmetric form with respect to the discrete S-duality (16):…”
Section: Toda Representationmentioning
confidence: 99%
“…Note that the parameters γ = (γ 1 , γ 2 ) are nothing but the components of the dual Weyl vector for given Lie algebra with the Cartan matrix (18). They may be represented in a explicitly symmetric form with respect to the discrete S-duality (16):…”
Section: Toda Representationmentioning
confidence: 99%
“…We note that fluxbrane "master equations" (245) may be obtained from the black brane ones (246) in the limit µ → ∞ . In [166], it was shown that black brane moduli functions may be obtained from fluxbrane ones at least for small enough charge densities. For different aspects of p-brane/fluxbrane correspondence, see [152,158].…”
Section: Of 54mentioning
confidence: 99%
“…Here as in [38] we parametrize the polynomials by using other parameters (here denoted B s ) instead of P s :…”
Section: Fluxbrane Polynomials For Lie Algebra Ementioning
confidence: 99%
“…The set of fluxbrane polynomials H s defines a special solution to open Toda chain equations [36,37] corresponding to a simple finite-dimensional Lie algebra G; see Ref. [38]. In Refs.…”
Section: Introductionmentioning
confidence: 99%